Improving Oral Health for the Elderly: an interdisciplinary approach - Lamster, Ira B. (Springer, 2017)
Two important oral health policy concerns in the United States are disparities in the oral disease burden and the inability of certain segments of the population to access oral health care. Both of these challenges are largely due to socioeconomic stratification in US society. As a consequence of the release of the surgeon general??'s report on oral health, there has been a call to action to improve the oral health of underprivileged groups who have difficulty accessing dental services. But in contrast to the extensive national attention focused on children??'s oral health in recent years, Ame.